2003
DOI: 10.1007/s100380300001
|View full text |Cite
|
Sign up to set email alerts
|

A novel splice site mutation in neonatal carnitine palmitoyl transferase II deficiency

Abstract: at the mRNA level in cases where a mutation leads to aberrant splicing or nonsense-mediated messenger decay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This presentation is fatal, leading to death in the neonatal period as was observed in our case (Albers et al, 2001a;Elpeleg et al, 2001;Gellera et al, 1992;Hug et al, 1991;Land et al, 1995;North et al, 1995;Pierce et al, 1999;Sharma et al, 2003;Smeets et al, 2003;Taroni et al, 1994;Vladutiu et al, 2002b;Witt et al, 1991;Zinn et al, 1991). Pregnancy may be complicated by oligohydramnios, and prenatal screening may show malformations including large ventricles, agenesis of the corpus callosum, intraventricular calcifications, and cystic dysplasia of the brain and the kidneys (Elpeleg et al, 2001;North et al, 1995).…”
Section: Clinical and Metabolic Features Of Cpt II Deficiencymentioning
confidence: 76%
See 1 more Smart Citation
“…This presentation is fatal, leading to death in the neonatal period as was observed in our case (Albers et al, 2001a;Elpeleg et al, 2001;Gellera et al, 1992;Hug et al, 1991;Land et al, 1995;North et al, 1995;Pierce et al, 1999;Sharma et al, 2003;Smeets et al, 2003;Taroni et al, 1994;Vladutiu et al, 2002b;Witt et al, 1991;Zinn et al, 1991). Pregnancy may be complicated by oligohydramnios, and prenatal screening may show malformations including large ventricles, agenesis of the corpus callosum, intraventricular calcifications, and cystic dysplasia of the brain and the kidneys (Elpeleg et al, 2001;North et al, 1995).…”
Section: Clinical and Metabolic Features Of Cpt II Deficiencymentioning
confidence: 76%
“…Genomic studies showed compound heterozygosity for the 534T ins/del 25 mutation and a GϾA splice mutation. This mutation, which is located in the intron 2 splice-acceptor site, was the first of its kind to be reported (Smeets et al, 2003). The L302fs (907_918ins) results in premature termination of the protein and truncation by about 350 amino acids and is also associated with the perinatal phenotype .…”
Section: Sigauke Et Almentioning
confidence: 99%
“…The neonatal onset form of CPT2 deficiency appears to be markedly more severe than the infantile onset form of the disease. Sixteen unrelated patients have been reported to date Elpeleg et al, 2001;Vladutiu et al, 2002a,b;Sharma et al, 2003;Smeets et al, 2003). 11 siblings were reported to have suddenly died most often during the first month of life.…”
Section: Cpt2 Deficienciesmentioning
confidence: 96%
“…Recently [9] the same mutation was described in a Moroccan family in which four out of five children, heterozygous for the mutation, died from the neonatal phenotype.…”
Section: Discussionmentioning
confidence: 78%